An Analysis of Linguistic Errors in the Translation of Children Story Books from Seri Dongeng Inspiratif Dunia Binatang by Yudhistira Ikranegara - Seno Sugeng Santoso; Abdur Rofik (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2023)
This study is aimed to analyze linguistic error in the translation of the children story books by Yudhistira Ikranegara in terms of syntax and semantics. This study used descriptive qualitative method. The collecting data of the research method includes reading, comparing, and providing marks. The result of this study: There are four classifications of syntax construction errors from the translation, namely: Syntax errors due to wastage of words or sentences; Syntax errors as a result improper use of punctuation marks; Syntax errors due to omission of affixation; Syntax errors due omission of words or phrases. Based on four classifications of syntax construction errors above that also cause the occurrence of three semantic errors, namely; total semantic error; partial semantic error; shift semantic errors.